Implementasi Fungsi-Fungsi Manajemen dalam Lembaga Pendidikan Islam (Studi Kasus Pengelolaan Madrasah Ibtidaiyah Islahul Muta’allim Pagutan) - Fathul Maujud (JURNAL PENELITIAN KEISLAMAN, 2018)
Keberhasilan lembaga pendidikan Islam (madrasah) dalam menyelenggarakan pendidikan sangat ditentukan oleh kemampuannya dalam mengimplementasikan fungsi-fungsi manajemen secara profesional. Artikel ini bertujuan untuk mendeskripsikan dan menganalisis implementasi fungsi-fungsi manajemen dalam pengelolaan Madrasah Ibtidaiyah (MI) Islahul Muta’allim Pagutan Kota Mataram. Untuk mendapatkan data, teknik yang digunakan yaitu observasi partisipan, wawancara mendalam, dan dokumentasi. Data yang diperolah analisis dengan model interaktif seperti yang dikembangkan oleh Miles dan Huberman (1994). Kesimpulan penelitian ini, bahwa dalam pengelolaan MI Ishlahul Muta’allim mengimplementasikan fungsi-fungsi manajemen antara lain fungsi perencanaan, pengorganisasian, dan pengawasan. Fungsi perencanaan dimulai dengan mekanisme penentuan arah dan tujuan yang hendak dicapai dengan melibatkan ketua yayasan, kepala sekolah, guru, dan komite. Fungsi pengorganisasian dilakukan dengan pembagian tugas dan tanggung jawab kepada seluruh civitas madrasah melalui rapat pembagian tugas sebelum tahun ajaran baru dilaksanakan. Fungsi pengawasan dilakukan dengan mengontrol kuantitas dan kualitas kerja personil melalui supervisi kelas, rapat kerja guru dan kepala madrasah, serta audit penggunaan anggaran dilakukan melalui rapat bersama komite madrasah. Title: The Implementation of Management Functions at Islamic Education Institutions (Case Study of Islahul Muta’allim Islamic Elementary School [MI] Management of Pagutan) Abstract: The objectives of this research are to describe and analyze the implementation of management functions in the management of Islahul Muta’allim Islamic Elementary School of Pagutan in Mataram city. To find the data, researcher used the data collection techniques namely: participant observation, in-depth interviews, and documentation. While for data analysis, researcher used data analysis techniques of interactive model developed by Miles and Huberman (1994). The conclusion of this research are; 1) Implementation of the planning function in the management of Islahul Muta’allim Islamic Elementary School is carried out with a mechanism of determination of the directions and objectives to be achieved by the school (madrasah), namely by determining the vision, mission and planned activities in the management of school (madrasah). The people involved in the planning of the school management program are the head of foundation, principal, teachers, and committees. 2) The implementation of the organizing function in the management of Islahul Muta’allim Islamic Elementary School is carried out with a mechanism of the distribution of jobs and responsibilities to the entire school civitas academica through the job sharing meeting for the all teachers and employees before the new school academic year is started. The facilities and equipments needed in the implementation of job are prepared by the school to support the school activities. Whereas for the determination of work methods and procedures, it is carried out based on the family system with the aim that all activities carried out are not neglected when there is a teacher who cannot fulfill the obligation for certain reasons. 3) The implementation of the supervisory function in the management of Islahul Muta’allim Islamic Elementary School is done by controlling the quantity and quality of personnel work, namely by conducting class supervision. For the investigation technique of the work relevance with school planning, it is done by discussing together to the problems which are considered heavy on the programs which have been undertaken and discussing problems through teacher and principal work meetings. While the budget use audit is carried out by prioritizing kinship carried out through joint meetings of school committee.